SISTEM INFORMASI PEMBUATAN SURAT KETERANGAN TIDAK MAMPU BERBASIS WEBSITE - Ahmad Su’aydi; Zainur Rahman; Firman Santoso (CV. Denasya Smart Publisher, 2025)
Jeru Curah Village Office is a government organization located in Jeru Curah Village, Panji Subdistrict, Situbondo District. Making a certificate is one of the services offered by the Jeru Curah Village Government to its citizens. Previously, certificates were made manually, which required residents to come to the Village Office to fill in the required documents and be verified by the manager. However, this process often experienced problems, such as residents' ignorance of the letter-making process, the need to visit the Village Office frequently due to limited working hours and not meeting certain requirements, thus reducing the effectiveness and efficiency of this service. A web-based certificate service information system should be created to overcome these problems. This research includes interviews, literature observation, and observation as data collection methods. The Waterfall method which has five stages of communication, planning, modeling, building, and implementing is used to design this system. The system was built using PHP programming language and MySQL database.Testing with Google Chrome shows that this approach provides reliable results. A web-based service information system that can facilitate the creation of certificate letters by village office officers, save work time, and facilitate the lives of citizens as a consequence of this research. easily simply input the required information, and is available online through the website.